Hypofractionated radiotherapy combined with a PD-1 inhibitor, granulocyte macrophage-colony stimulating factor, and thymosin-α1 in advanced metastatic solid tumors: a multicenter Phase II clinical trial - Jiamin Yu; Li Yin; Wenjie Guo; Qiang Wang; Juying Liu; Lansheng Zhang; Hongxun Ye; Jianhong Xia; Youyou Xia; Jianfeng Wu; Wanwei Wang; Yanguang Yang; et al. (Cancer Immunology, Immunotherapy)
Abstract Purpose This multicenter Phase II clinical study assessed the efficacy and safety of hypofractionated radiotherapy (HFRT) in combination with a PD-1 inhibitor, granulocyte macrophage-colony stimulating factor (GM-CSF), and thymosin-α1 in patients with heavily treated metastatic solid tumors. Methods Patients were enrolled between September 2022 and May 2024. HFRT was administered to targeted tumors, and GM-CSF was administered for 14 days from day 1 of radiotherapy. Thymosin-α1 was injected concurrently twice weekly until disease progression. Immunotherapy with camrelizumab was started following HFRT and repeated every 3 weeks. GM-CSF was administered daily for 7 days before each cycle of immunotherapy. Results By June 15, 2024, there were 37 study participants. The median follow-up duration was 5.97 months (range 0.40–20.9). Median progression-free survival was 3.5 months (95% confidence interval 2.73–4.23) in the intention-to-treat population. The objective response rate was 23.08%, and the disease control rate was 65.38%. Overall survival data are not yet mature. Abscopal effects were observed in 6 patients (23.08%); four of whom achieved a partial response. Patients who achieved a partial response were significantly more likely to have an abscopal effect( P = 0.025). The group with a lower baseline neutrophil–lymphocyte ratio had a significantly lower risks of distant metastasis and death( P = 0.024). Seventeen adverse reactions were reported, including six grade 3 or 4 adverse events. There were no grade 5 adverse events. Conclusion In conclusion, the trends in efficacy observed in our study are promising; however, well-designed protocols are essential to validate these findings.